Pengaruh Good Corporate Governance dan Leverage Terhadap Manajemen Laba Pada Perusahaan PT Unilever Indonesia Tbk Periode 2019-2024: The Influence of Good Corporate Governance and Leverage on Profit Management at the Company PT Unilever Indonesia Tbk for the 2019-2024 Period - Nadine Maritza Septiani; Bunga Citra Lestari (AMANAH: Jurnal Manajemen Keuangan Sektor Publik, 2026)
This study analyzes the effect of Good Corporate Governance (GCG) and leverage on earnings management at PT Unilever Indonesia Tbk for the period 2019-2024 using a quantitative approach based on a single-company case study. Secondary data were obtained from the company's annual financial statements. Earnings management is proxied by total accruals, GCG is measured through the proportion of independent commissioners, independent audit committees, and board size, while leverage is measured using the Debt to Equity Ratio (DER). Multiple linear regression analysis shows that partially, GCG and leverage do not have a significant effect on earnings management. However, simultaneously, GCG and leverage have a significant effect (sig = 0.032) with an R² value of 0.979. Considering the limited number of observations and the presence of multicollinearity, the study results are interpreted cautiously and emphasize the importance of evaluating governance and funding structure in an integrated manner.